2016
DOI: 10.2174/1573396311666151026110148
|View full text |Cite
|
Sign up to set email alerts
|

Safe Infant Sleep Interventions: What is the Evidence for Successful Behavior Change?

Abstract: Sudden infant death syndrome (SIDS) and other sleep-related infant deaths, such as accidental suffocation and strangulation in bed and ill-defined deaths, account for >4000 deaths annually in the USA. Evidence-based recommendations for reducing the risk of sleep-related deaths have been published, but some caregivers resist adoption of these recommendations. Multiple interventions to change infant sleep-related practices of parents and professionals have been implemented. In this review, we will discuss illust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
93
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 50 publications
1
93
1
2
Order By: Relevance
“…Pediatricians and family practice providers typically have little professional interaction with pregnant women until after the birth of the infant. Nurses, particularly those in nursery and postnatal settings such as Women, Infants, and Children (WIC) programs, have been shown to be trusted sources of information related to newborn care and can influence the infant safe sleep decisions that parents make . Prenatal care providers are also a valuable resource as preparations are being made for the infant's arrival.…”
Section: Introductionmentioning
confidence: 99%
“…Pediatricians and family practice providers typically have little professional interaction with pregnant women until after the birth of the infant. Nurses, particularly those in nursery and postnatal settings such as Women, Infants, and Children (WIC) programs, have been shown to be trusted sources of information related to newborn care and can influence the infant safe sleep decisions that parents make . Prenatal care providers are also a valuable resource as preparations are being made for the infant's arrival.…”
Section: Introductionmentioning
confidence: 99%
“…2 Some of the efforts to reduce deaths have included public service campaigns, 3 community programs and initiatives, safe sleep education and modeling in the hospital setting, and identifying and addressing barriers to safe sleep. 4,5 The direct impact of individual interventions on the overall infant mortality rate, measured as infant deaths per 1000 live births, is difficult to determine.State Child Fatality Review (CFR) teams and Fetal and Infant Mortality Review (FIMR) teams are public health strategies used to understand child and infant deaths at the local level through a multidisciplinary team review. A systematic process is used to collect and analyze data from multiple sources, identify systems-related factors and risks, and make recommendations to improve systematic care, address resource gaps in the community, and reduce preventable deaths.…”
mentioning
confidence: 99%
“…2 Some of the efforts to reduce deaths have included public service campaigns, 3 community programs and initiatives, safe sleep education and modeling in the hospital setting, and identifying and addressing barriers to safe sleep. 4,5 The direct impact of individual interventions on the overall infant mortality rate, measured as infant deaths per 1000 live births, is difficult to determine.…”
mentioning
confidence: 99%
“…Unannounced direct observations of infant care practices at a family’s home would be the preferred approach but would be challenging to accomplish. 10 …”
mentioning
confidence: 99%
“…Other studies have shown improvements to safe sleep practices following postpartum nursing education and modeling. 10,11 It could be that the selected hospitals provided safe sleep education that was as effective as the NQI safe sleep intervention. It is also possible that mothers receiving the intervention in the hospital may not have retained the information after they went home.…”
mentioning
confidence: 99%